Mode control in planar waveguide grating couplers with double surface corrugation - Xiao, Zhe (2013)
Grating couplers with double surface corrugation are proposed to adjust the resonance behavior of both TE and TM modes simultaneously. Through proper selection of parameters, we designed a polarization-independent grating coupler operating at 1.55-μm telecommunication wavelength. Efficiency is achieved at around 55% for both TE and TM modes, and the polarization-dependent loss is <; 0.05 dB within the spectral window from 1544 to 1561 nm. Furthermore, a double-channel grating coupler is proposed to excite the TE and TM modes at 1.31 and 1.49 μm, respectively. The achievable efficiency is around 60% for both channels with good uniformity.